Einstein Snake and Ladder Game: A Game-Based Physics Learning Media for Interactive and Enjoyable Classrooms - Lalu Azikri Amrullah; Nanda Sulistia Wardani; Elgarisna Rambunewa; Ahmad Harjono; Gunawan Gunawan (Indonesian, 2024)
This article discusses innovations in physics learning methods through the use of game-based media, specifically a snakes and ladders game designed with educational elements. In the context of an ever-evolving educational landscape, traditional approaches are often considered less effective in capturing student interest, particularly in complex subjects like physics. Therefore, this research developed a media tool called